A study of knowledge workers and productivity in the commercial banking industry in Kuching / Rosita Suhaimi ...[et al.] - Suhaimi, Rosita; Song, Saw Imm; Chong, Vui Hok; Chong, Fen Nee (2002)
This study seeks to understand the relationship between knowledge workers, the banking work environment and the impact of the work environment on the productivity of the commercial banks in Kuching. The definition of the work environment includes Peter Drucker's 6 factors, namely task identification, autonomy , continuous innovation, continuous learning, importance of quality and employee as asset. Productivity of banks is measured using productivity measures such as counter transactions per day, loan applications processed/approved, values of deposits, value of credit approved, gross profit before tax, and average cost per employee.